Implementasi model circuit learning dalam meningkatkan keterampilan menulis teks nonfiksi pada peserta didik kelas V sekolah dasar - Safitri Niswatur Rohmah; Retno Winarni; Muhammad Ismail Sriyanto (Didaktika Dwija Indria, 2020)
This research aims to improve nonfiction text writing skills by implementing a Circuit Learning Model. The Type of this research is Classroom Action Research with 2 cycles. The subject of this research were 24 fifth grade students of Ta’mirul Islam Surakarta Primary School during 2018/2019 academic year. Data collection in this research uses interviews, tests, observations, and documentation with triangulation and data analysis of content. Qualitative data analysis used Miles- Huberman interactive analysis model. While, quantitative data analysis are the result of nonfiction text writing skills. The pre-action cycle resulting in percentage of 4,2% in classically, continued with the first cycle with the  percentage of 33,3% in classical and in the last cycle resulting in percentage of 95,5% classically. Based on the result obtained, it can be concluded that nonfiction text writing skills of Ta’mirul Islam Surakarta Primary School in the 2019/ 2020 academic year can be upgraded through the implementation of the Circuit Learning Model. <w:LsdException Locked="false" Priority="46" Nam